Optimization Of Potassium Hydroxide (Koh) Etching On The Fabrication Of P-Type Silicon Nanowire Transistor Patterned By Atomic Force Microscopy Lithography - Abdullah, Ahmad Makarimi (2012)
Silicon nanowire transistor (SiNWT) has been successfully fabricated by atomic force microscopy (AFM) lithography through wet etching process. The silicon on insulator (SOI) <100> wafer was used as a starting material. Prior to use, the SOI wafer was cleaned by using ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2), nitric acid (HNO3) and Di-Ionize water (DIW) and diluted hydrofluoric acid (HF) to remove the organic, inorganic contaminants and native oxide from the wafer surface. A non-contact AFM mode was chosen to perform the AFM lithography process on pre-cleaned SOI wafer. The SiNWT structure was designed by using raster programming. A conductive AFM tip (Cr/Pt cantilever tip) was used to fabricate SiNWT patterns on the SOI surface based on pre-designed structures. The patterned structure (as oxide mask) was etched through two steps of wet etching processes. First, the potassium hydroxide (KOH) and isopropyl alcohol (IPA) were used as the etchant solution for silicon removing. It was found that etchant solution of 30 wt% KOH + 10 vol% IPA, etching time of 22 seconds and solution temperature of 65 oC as an optimum etching parameters. In the second step, diluted HF was used to remove oxide mask in order to produce a completed SiNWT device. The fabricated SiNWT was characterized by AFM, SEM, EDX, 3D laser microscope, FIB-TEM and semiconductor parameter analyzer. From current-voltage characteristics, it was proven that the device is working as a p-type SiNWT.